Freeform direct laser writing of versatile topological 3D scaffolds enabled by intrinsic support hydrogel. Issue 12 (7th October 2021) - Hasselmann, Sebastian; Hahn, Lukas; Lorson, Thomas; Schätzlein, Eva; Sébastien, Isabelle; Beudert, Matthias; Lühmann, Tessa; Neubauer, Julia C.; Sextl, Gerhard; Luxenhofer, Robert; Heinrich, Doris
Abstract : By combining a photocurable and a thermogelling hydrogel, it is possible to perform 3D freeform structuring via two-photon-polymerization and to manufacture concatenated parts without additional support structures. Abstract : In this study, a novel approach to create arbitrarily shaped 3D hydrogel objects is presented, wherein freeform two-photon polymerization (2PP) is enabled by the combination of a photosensitive hydrogel and an intrinsic support matrix. This way, topologies without physical contact such as a highly porous 3D network of concatenated rings were realized, which are impossible to manufacture with most current 3D printing technologies. Micro-Raman and nanoindentation measurements show the possibility to control water uptake and hence tailor the Young's modulus of the structures via the light dosage, proving the versatility of the concept regarding many scaffold characteristics that makes it well suited for cell specific cell culture as demonstrated by cultivation of human induced pluripotent stem cell derived cardiomyocytes.